2011
DOI: 10.1590/s1517-83822011000100017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification of methanogenic archaea from Surti buffaloes (bubalus bubalis), reveals more hydrogenotrophic methanogens phylotypes

Abstract: Methane emissions from ruminant livestock are considered to be one of the more potent forms of greenhouses gases contributing to global warming. Many strategies to reduce emissions are targeting the methanogens that inhabit the rumen, but such an approach can only be successful if it targets all the major groups of ruminant methanogens. Therefore, a thorough knowledge of the diversity of these microbes in breeds of buffaloes, as well as in response to geographical location and different diets, is required. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 57 publications
(55 reference statements)
3
7
0
Order By: Relevance
“…buffalo and other ruminants. However, some studies conducted in India reported that methanogen community in buffalo was dominated by Methanomicrobium (Chaudhary and Sirohi 2009;Singh et al 2011). The present study further verified that ruminal methanogen community of buffalo in China is quite similar to other ruminants.…”
Section: Discussionsupporting
confidence: 84%
“…buffalo and other ruminants. However, some studies conducted in India reported that methanogen community in buffalo was dominated by Methanomicrobium (Chaudhary and Sirohi 2009;Singh et al 2011). The present study further verified that ruminal methanogen community of buffalo in China is quite similar to other ruminants.…”
Section: Discussionsupporting
confidence: 84%
“…The distribution frequency of Mm. mobile in cattle and buffaloes was in consonance with the global data sets [5,12,49] but there is a disagreement with previous reports of unprecedented higher distribution of Methanomicrobium in cattle [51,52] and buffaloes [53][54][55]. As these studies used PCR and cloning based approach; the primer bias could be one of the reason for the disagreement in Methanomicrobium abundance.…”
Section: Discussionmentioning
confidence: 58%
“…Earlier phylogenetic study based on 16S rRNA gene in metagenome of Indian bovine, suggested that more than 50% clones belonged to the order Methanomicrobiales [25]. In a study by Shin (2004) the predominant rumen methanogen in the rumen fluid and rumen epithelium were from the family Methanomicrobiaceae [26].…”
Section: Discussionmentioning
confidence: 94%